2002
DOI: 10.1136/sti.78.1.31
|View full text |Cite
|
Sign up to set email alerts
|

STD in Bangladesh's trucking industry: prevalence and risk factors

Abstract: Objectives: This study characterises the prevalence of a broad spectrum of sexually transmitted diseases (STDs) (herpes simplex virus 2, syphilis, chlamydia, gonorrhoea), and examines associations between risk factors and infection in men working in Bangladesh's trucking industry. Given the high risk sexual behaviours of truck drivers and helpers in many contexts, as well as the direct health effects of STDs and their role in facilitating HIV transmission, it is important to understand the prevalence of STDs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 17 publications
1
14
1
2
Order By: Relevance
“…9 A study among truck drivers and helpers in Bangladesh reported that 54% of them had sexual relation with FSWs in the past year and had a higher prevalence of herpes simplex virus type 2 (25.8%) and serologic syphilis (5.7%). 14 The prevalence of syphilis among men was 4.1%, being only slightly lower to that found among truckers (5.4%) in an earlier study in the Dhaka city 14 ; however, the prevalence rates of gonorrhea and chlamydial infection in this study were found to be higher. Both studies used nucleic acid amplification tests in diagnosing Neisseria gonorrhoeae and Chlamydia trachomatis.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…9 A study among truck drivers and helpers in Bangladesh reported that 54% of them had sexual relation with FSWs in the past year and had a higher prevalence of herpes simplex virus type 2 (25.8%) and serologic syphilis (5.7%). 14 The prevalence of syphilis among men was 4.1%, being only slightly lower to that found among truckers (5.4%) in an earlier study in the Dhaka city 14 ; however, the prevalence rates of gonorrhea and chlamydial infection in this study were found to be higher. Both studies used nucleic acid amplification tests in diagnosing Neisseria gonorrhoeae and Chlamydia trachomatis.…”
Section: Discussioncontrasting
confidence: 51%
“…13 Studies conducted among truck drivers and helpers in Bangladesh revealed a high prevalence of sexual risk behaviors and certain STIs; 54% of the 388 truckers in the Tejgaon truck stand, one of the largest truck stands in Bangladesh, had sexual encounters with a commercial sex worker (CSW) in the past year, whereas 50% of the married males in the sample had sex with both a CSW and their wife during the same period. 14 Because truckers in Bangladesh, like in other countries, were found at higher risk for STI/ HIV, assessment of STI risk behaviors and infection status in bridging populations with close contacts with truckers remains important to guide targeted STI/HIV prevention intervention.…”
mentioning
confidence: 99%
“…In fact, earlier studies in India [16,29] and other parts of South Asia [30] revealed associations between low condom use and STI prevalence, particularly HSV-2 and, to a lesser extent, syphilis.…”
Section: Discussionmentioning
confidence: 95%
“…1,2 High rates of STIs and HIV have been observed among long-distance truck drivers in India and Bangladesh, where truck drivers are implicated in the spread of STIs and HIV into rural areas and areas surrounding international border crossings. [7][8][9][10][11] Results from studies in Eastern Europe suggest risky behavior and increased syphilis rates among truck drivers. 12,13 Additionally, studies among truck drivers in Brazil show low levels of perceived risk of infection despite high rates of syphilis and high levels of risky behaviors, e.g., unprotected sex with multiple partners, including commercial sex workers, and high levels of drug use.…”
mentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Evidence suggests that the spread of HIV throughout central Africa was facilitated by truck traffic along the Kinshasa-Mombasa highway. 1,2 High rates of STIs and HIV have been observed among long-distance truck drivers in India and Bangladesh, where truck drivers are implicated in the spread of STIs and HIV into rural areas and areas surrounding international border crossings.…”
mentioning
confidence: 99%